Meta-Analysis of Emergencies in ENT and its Management: An Ayurvedic Approach - Dhanashree Gole; Nilakshi Pradhan (AYUSHDHARA, 2022)
Emergencies in ENT are common occurrence. Early diagnosis and management result in reduction in morbidity and mortality. In this study we have explained initial assessment, medical records, diagnosis on admission and outcome of emergency care. A total of patients were attended as an emergency in our institution’s hospital apart from OPD timing i.e., (9-4pm). The most common emergencies among pediatric age group were foreign body in ear, nose, and throat. The other most commonly encountered emergencies were RTA patients with cut or tear wound, epistaxis. In traditional text of Ayurveda mentioned terms like: Vegavastha Dhatugat Avastha, Upadrav, Asadhya Lakshanas, Agantuj Vyadhi, Sadhya, Ashu etc. for emergency conditions which are needed to be taken care of immediately The ENT emergencies play a key role in the management of life-threatening conditions requiring immediate evaluation and management. It is important to prioritize the emergency/non emergency cases in order to ensure proper care is given to the emergency cases.